Frequency regulation for microgrid using genetic algorithm and particle swarm optimization tuned STATCOM - Saxena N.K.; Gao W.D.; Kumar A.; Mekhilef S.; Gupta V. (John Wiley and Sons Ltd, 2023)
Asynchronous generators; Controllers; Distributed power generation; Electric current regulators; Electric power transmission networks; Errors; Flexible AC transmission systems; Frequency response; Genetic algorithms; IEEE Standards; Iterative methods; MATLAB; Power control; Reactive power; Static synchronous compensators; Classical methods; Compensator current; Current controller; Distributed generators; Frequency regulations; Genetic algorithm and particle swarm optimizations; Microgrid; Power load; Squirrel cage induction generators; Static synchronoi compensator; Particle swarm optimization (PSO)